Intrathrombus Fibrin Attenuates Spatial Sorting of Phosphatidylserine Exposing Platelets during Clotting Under Flow - Trigani, Kevin T.; Diamond, Scott L. (Thrombosis and Haemostasis, 2020)
Background As thrombosis proceeds, certain platelets in a clot expose phosphatidylserine (PS) on their outer membrane. These PS+ platelets subsequently sort to the perimeter of the mass via platelet contraction. It remains unclear how thrombin and fibrin may alter PS+ platelet sorting within a clot.Objective We investigated the role of fibrin in PS+ platelet sorting.Methods We used an 8-channel microfluidic assay of clotting over collagen (±tissue factor) at 100 s−1 initial wall shear rate. Temporal PS+ platelet sorting was measured using a Pearson's correlation coefficient between the annexin V distribution in a clot at 9 versus 15 minutes. Spatial PS+ platelet sorting was measured using an autocorrelation metric of the final annexin V distribution.Results By 6 minutes, PS+ platelets were distributed throughout the platelet deposits and became highly spatially sorted by 15 minutes when thrombin and fibrin were blocked with Phe-Pro-Arg-chloromethylketone (PPACK). Fibrin polymerization (no PPACK) attenuated temporal and spatial PS sorting and clot contraction. With Gly-Pro-Arg-Pro (GPRP) added to block fibrin polymerization, PS sorting was prominent as was clot contraction. Exogenously added tissue plasminogen activator drove fibrinolysis that in turn promoted clot contraction and PS sorting, albeit to a lesser degree than the PPACK or GPRP conditions. Clots lacking fibrin displayed 3.6 times greater contraction than clots with fibrin.Conclusion PS sorting correlated with clot contraction, as previously reported. However, fibrin inversely correlated with both percent contraction and PS sorting. Fibrin attenuated clot contraction and PS sorting relative to clots without fibrin.
Keywords: contraction; fibrin; phosphatidylserine; platelet; thrombin